(untitled) (Jurnal Geologi Pertambangan (JGP), 2016)
The research area covers the administration of the Pacitan District, East Java Province. Geological data, such as lithological data, structural data, contour data and alteration, were used in analyses and making evidence maps. The geological data yield six evidence maps such as NE-SW lineament, NW-SE lineament, hostrock, heat source, kaolinite alteration and iron oxide alteration maps. Evidence maps were analyzed by weight of evidence methods to result in favorable maps, where the validity was tested using conditional independence (CI), the pairwise and overall tests. Then, the analyses produced a posterior probability map. Posterior probability map (mineral potential maps) was validated by checking field to determine the next exploration target zone cluster. Posterior probability map (after validation) / favorable map predicted approximately 27,61% (389.83 km2) including the favorable zone and approximately 72,39% (1021,79 km2) including non favorable zones. Favorable zones are divided into three classes. The target areas were divided into five clusters areas of mineralized potential zone. Keyword: GIS, weight of evidence, mineral potential mapping, Pacitan District